Modeling and Optimization of Phenolic Compounds from Sage (Salvia fruticosa L.) Post-Distillation Residues: Ultrasound- versus Microwave-Assisted Extraction - Maria Irakli; Elisavet Bouloumpasi; Stamatia Christaki; Adriana Skendi; Paschalina Chatzopoulou (MDPI AG, 2023)
The essential oil production of Salvia fruticosa L. generates considerable amounts of post-distillation solid residues (PRES) which are rich in phenolic compounds. In the present work, the recovery of phenolic antioxidants from PRES by using Microwave-Assisted Extraction (MAE) and Ultrasound-Assisted Extraction (UAE) were separately optimized, according to the Box-Behnken experimental design. The optimization was based on extraction yield, total phenolic content (TPC), total flavonoid content (TFC), rosmarinic acid (RMA), carnosol (CARO), carnosic acid (CARA), and antioxidant activity. The optimal processing parameters were 72% and 68% ethanol, a 15- and 10-min extraction time, a 40 °C and 47 °C extraction temperature, and a 1:30 and 1:10 solid-to-solvent ratio, for MAE and UAE, respectively. Results showed that the levels of RMA, CARO, and CARA in UAE extracts were influenced mainly by ethanol concentration, extraction time, and extraction temperature, while MAE extracts were only influenced by the first two factors. Experimenting with the optimal conditions revealed MAE as more effective than UAE in the recovery of RMA and CARA. The experimental values were in good agreement with the predicted ones, indicating model efficacy in MAE and UAE optimization to effectively extract phenolic compounds from PRES for their further application in food and pharmaceutical industries.